2011
DOI: 10.1017/s1742170511000184
|View full text |Cite
|
Sign up to set email alerts
|

Controlled studies further the development of practical guidelines to manage dodder (Cuscuta gronovii) in cranberry production with short-term flooding

Abstract: Flooding is an inexpensive cultural practice used for pest management in Massachusetts cranberry (Vaccinium macrocarpon Ait.) production. This project examined the use of short-term floods ( < 72 h) for dodder (Cuscuta gronovii Willd.) management under controlled conditions. Using incubators, seed was submerged in water for 0, 24 and 48 h at 10, 15 and 20 C (simulating spring water temperatures) and 0, 12, 24, 36 and 48 h at 15, 20 and 25 C (simulating summer water temperatures). Two 1-year controlled studies … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Cuttings for 'Stevens' and 'Howes' were taken from established cranberry farms located in Wareham, MA. Cranberry plants were cut and rooted according to previously published protocols (O'Connell et al, 2011). During establishment (May through September), plants were fertilized once per week with 15N-7.0P-14.1K (833 mg • L -1 ) by drenching the soil with the fertilizer solution.…”
Section: Methodsmentioning
confidence: 99%
“…Cuttings for 'Stevens' and 'Howes' were taken from established cranberry farms located in Wareham, MA. Cranberry plants were cut and rooted according to previously published protocols (O'Connell et al, 2011). During establishment (May through September), plants were fertilized once per week with 15N-7.0P-14.1K (833 mg • L -1 ) by drenching the soil with the fertilizer solution.…”
Section: Methodsmentioning
confidence: 99%
“…Glass covers were placed over dishes and sealed with Parafilm (Parafilm M, Pechiney Plastic Packaging, Menasha, WI 54952) strips to reduce evaporative water loss. Dishes were incubated (Fisher Low Temperature Incubator Model 307, Fisher Scientific) in the dark at 23 C and were checked periodically for 3 wk after scarification to evaluate seed germination (Benvenuti et al 2005;O'Connell et al 2011). Germinated seeds were removed from the dishes and counted, and the percentage of germination was calculated.…”
Section: Methodsmentioning
confidence: 99%
“…Field studies indicated that 24-48 h floods in mid-May may offer a sustainable option that could be integrated into the overall management plan for dodder [15]. Subsequent work indicated that the floods may retard dodder stem growth rather than reduce seed germination [79].…”
Section: Late Water Short Spring Floods Summer Floods and Fall Floodsmentioning
confidence: 99%